The oral health of people with serious mental illness - Jones, Hannah F. (2016)
The physical health needs of people with serious mental illness have been neglected for a long time (1), this has initiated the development of guidelines and recommendations from the British Society for Disability and Oral Health (BSDH) for the oral health care for people with serious mental illness (2). Guidelines recommend monitoring and advice and although they are well meaning, randomised controlled trial evidence to support the recommendations is missing (3, 4). Cochrane systematic reviews found no randomised controlled trials of oral health advice or monitoring for people with serious mental illness (5). A Cochrane systematic review of general physical health advice interventions for people with serious mental illness (6) found evidence to suggest such interventions could lead to people accessing more health services. For oral health there is some survey evidence to suggest regular dental check-ups have been found to be associated with better oral health (7), so if a monitoring and advice intervention can influence someone with serious mental illness to visit a dentist this may in turn improve their oral health.